Occupational Stress Among Health Worker in a National Dermatology Hospital in Vietnam, 2018 - Nguyen Ngoc, Anh; Le Thi Thanh, Xuan; Le Thi, Hue; Vu Tuan, Anh; Nguyen Van, Thanh (Frontiers in Psychiatry, 2020)
A cross-sectional study was conducted among 171 doctors and nurses in a National Dermatology hospital using the Karasek's Job Content Questionnaire which has been validated in Vietnamese (JCQ-V), to assess the prevalence of occupational stress and to explore the association with some associated factors among them. The result showed that doctors and nurses with occupational stress accounted for 6.4%. This proportion was higher among nurse compared to doctor (8.0% vs. 2.2%); among those with diploma literacy compared to bachelor and above (10.6% and 2.3%). This rate was also higher in health workers under 30 years old (12.9%), health workers under 5 years at work (12.1%), working night shift from 3-4 nights (33.3%), temporary employment (12.8%), heavy workload occasionally (12.5%), working hard occasionally (17.2%) compared to those in the comparison groups with p value <0,05. This prevalence concentrated in some departments such as surgery (11.9%); internal medicine (6.7%); Dermatology and others (1.5%). The study has not found the significant association between the prevalence of occupational stress and heavy workload and skill worked. Therefore, it is essential for hospital should conduct screening all doctors, nurses and medical staffs to identify subjects having occupational stress and give appropriate intervention.